Expression of Neuron-Associated Tumor Necrosis Factor Alpha in the Brain is Increased During Persistent Pain. Issue 4 (1st July 2002) - Covey, William C.; Ignatowski, Tracey A.; Renauld, Amy E.; Knight, Paul R.; Nader, Nader D.; Spengler, Robert N.
Abstract : Background and Objectives: Evidence implicates the pleiotropic cytokine tumor necrosis factor alpha (TNFα) in the pathogenesis of persistent pain. The present study employs a chronic constriction injury (CCI) model of neuropathic pain to examine TNFα production in the central nervous system (CNS) and in the periphery in this pain model. Methods: CCI-induced hyperalgesia is assessed by measuring the nociceptive threshold using the hot-plate test. The development of hyperalgesia is correlated to levels of TNFα by assessing: bioactive TNFα in homogenates of sciatic nerves, cervical spinal cord, thoracolumbar spinal cord, as well as in plasma using the WEHI-13 variant cytotoxicity bioassay; and mRNA for TNFα in sections of locus coeruleus by in situ hybridization. Results: We have previously demonstrated that TNFα bioactivity in the region of the brainstem containing the locus coeruleus is increased concurrent with the development of hyperalgesia, returning to baseline values by day 14, when hyperalgesia has ceased. Constitutive levels of TNFα are demonstrated in the plasma, sciatic nerves, and cervical and thoracolumbar spinal cord of control rats, sham-operated rats, and rats undergoing CCI. Levels of TNFα are significantly elevated in the injured sciatic nerve by day 8 postligature placement, concurrent with maximal hyperalgesia, and remain elevated when hyperalgesia has abated at day 14 postligature placement. Additionally, TNFα activity is increased in the thoracolumbar region of the spinal cord by day 4 postligature placement and remains elevated during hyperalgesia (day 8), as well as after hyperalgesia has dissipated (day 14). The increase in TNFα expression is specific to discrete regions of the CNS, rather than being the result of a systemic inflammatory response, since TNFα bioactivity in plasma is, in fact, decreased in rats undergoing CCI. Additionally, accumulation of mRNA specific for TNFα is significantly increased in neurons within a region of the brain containing the locus coeruleus at days 2, 8, and 14 postligature placement, contemporaneous with the development of hyperalgesia. Conclusions: The increases in TNFα within regions of the brain and spinal cord that are associated with adrenergic neuron function, as well as with modulation of pain perception, and the time course and distribution of the increases in TNFα accumulation support a neuromodulatory role for TNFα within the CNS in the development and maintenance of neuropathic pain.